2017
DOI: 10.1556/2006.6.2017.076
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia predicts loss chasing for people at risk for problem gambling

Abstract: Background and aimsThe aim of this research was to investigate the relationship between alexithymia and loss-chasing behavior in people at risk and not at risk for problem gambling.MethodsAn opportunity sample of 58 (50 males and 8 females) participants completed the Problem Gambling Severity Index and the Toronto Alexithymia Scale (TAS-20). They then completed the Cambridge Gambling Task from which a measure of loss-chasing behavior was derived.ResultsAlexithymia and problem gambling risk were significantly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Gambling problems were assessed mostly with South Oaks Gambling Screen [20,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37], which is the most used instrument in research literature. In four studies the Canadian Problem Gambling Index [21,38], the Problem Gambling Severity Index [39] or the Kurzfragebogen zum Glücksspielverhalten [29] were used, some of which by adding DSM criteria for gambling disorder.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Gambling problems were assessed mostly with South Oaks Gambling Screen [20,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37], which is the most used instrument in research literature. In four studies the Canadian Problem Gambling Index [21,38], the Problem Gambling Severity Index [39] or the Kurzfragebogen zum Glücksspielverhalten [29] were used, some of which by adding DSM criteria for gambling disorder.…”
Section: Resultsmentioning
confidence: 99%
“…Bibby and Ross [39] provided evidence for understanding a specific aspect of problem gambling, the loss chasing behavior, namely the tendency to continue to bet in an attempt to recover an earlier loss. They found that bettors at risk of problem gambling and high in alexithymia were most likely to chase losses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alexithymia Alexithymia is a personality trait describing the tendency to have difficulties in processing emotions [71,72]. It is not a social cognitive function per se, but its level seems to impact the social functioning of the individuals, as well as their ability to identify emotional facial expressions [62].…”
Section: Factors That Could Impact Sc Assessmentmentioning
confidence: 99%